Realization of medical image data transfer learning based on MATLAB - HUANG Xiaxuan; HUANG Tao; YUAN Shiqi; HE Ningxia; WU Wentao; LYU Jun (Yixue xinzhi zazhi)
Objective To discuss how to implement the application of medical image data on transfer learning based on MATLAB.Methods Taking MIMIC-CXR for example, 500 X-ray images of positive and the same number negative pleural effusion were randomly selected as the total data set, and the MATLAB software transfer learning method based on the ResNet network model was used for multiple training, calculating the AUC value to evaluate the accuracy of the model training for pleural effusion image classification.Results The pleural effusion imaging test set and training set used in this study were evenly distributed. Some training models had an accuracy rate of 80%, and the loss rate dropped to below 20%. The highest accuracy rate in training with 250 iterations was up to 100%, which took about 2 minutes and 38 seconds. Based on the prediction results of image data transfer learning obtained in this model training, the highest AUC value was 93.53%.Conclusion The transfer learning method of the ResNet network model can realize the effective combination and enhance-ment of model construction and medical imaging data training, and the model has good predictive performance, which provides a certain basis for clinicians in the early diagnosis of pleural effusion.